PENGARUH FIRM SIZE DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 – 2017) - Sri Wahyuni; Makhdalena Makhdalena; RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: this study aims to look at the effect of firm size and leverage on financial performance both simultaneously and partially in the food and beverage sub- sector companies listed on the Indonesia Stock Exchange for the period 2013 – 2017. The population of this study is all food and beverage sub – sector companies listed on the Indonesian Stock Exchange in the period 2013 – 2017 where the data is examined by census. This study uses secondary data sourced from the Indonesian Capital Market Directory (ICMD). The data analysis technique used is path analysis with the help of the statistical package for social science (SPSS). The results of the study show that firm size and leverage simultaneously influence the company’s financial performance. Firm size partially has a positive effect on the company’s financial performance while leverage has a negative effect on financial performance.Key Words: Firm Size, Leverage, Company’s Financial Performance